The Effect of Communication and Physical Work Environment on Employee Performance: : Study at a Vehicle and Machinery Industry Company in Bandung - Harnum Lathifan; Asep Rochyadi Suherman (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The workplace environment significantly influences employee performance. Employee productivity is directly impacted by the work environment, which enhances performance. As a fundamental human activity, communication plays a crucial part in social relationships; as a result, its impact on the workplace is crucial. Employee performance is more productive when there is more built-in communication between departments. The primary objective of this study is to investigate the impact of communication and the physical work environment on employee performance within car and machinery manufacturing enterprises located in Bandung. The present investigation employed a nonprobability sampling technique. The utilization of sample acquisition methodology becomes crucial when the population size is constrained or when the research objective is to achieve the highest level of generalizability. Censuses are another name for saturated sampling, in which the entire population—61 people in this case—serves as a sample. Descriptive and verifiable research methodology is used. Utilized data collection methods include observation, questionnaire distribution, and interviewing. Multiple linear regression, multiple correlations, F-test, T-test, coefficient of determination, partial determination coefficient, and hypothesis testing are the data analysis techniques used. According to the research findings, a vehicle and machinery sector firm in Bandung can have good communication, a physical work environment, and staff performance. Employee performance is strongly influenced by communication and the physical work environment, with the remaining influences coming from elements that were not studied.